PENERAPAN TWO WAY MANOVA DALAM MELIHAT PERBEDAAN LAMA STUDI DAN INDEKS PRESTASI MAHASISWA REGULER 2009 BERDASARKAN JALUR MASUK DAN AKTIVITAS MAHASISWA FKM USU TAHUN 2013 - Jehan Mutiarany; Abdul Jalil Armi Arma; Maya Fitria (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
MANOVA is an extension of the Analysis of Variance (ANOVA), which have long been widely used in various fields of science. Technically, MANOVA can be interpreted as a statistical method to explore the relationship between several independent variables are categorical type nominal or ordinal scale with multiple dependent variables are type numerical interval or ratio scale. This research aims to determine whether there are differences in length of study and student achievement index based on admission selection and student activity which was followed by regular student 2009 Public Health Faculty University of Sumatera Utara in 2013. This research was conducted by survey method with a correlation study is to find out relationship between the dependent and independent variables in a group of subjects. The results of the analysis using the Two-Way MANOVA test for admission selection variable at the significance level (α) of 0,05 indicates that there are significant differences on variables length of study and student achievement index which is tested simultaneously based on admission selection regular students 2009 Public Health Faculty University of Sumatera Utara with a significance value of Pillai’s Trace is 0,013. For a student activity variables at significance level (α) of 0,05 indicates that there is no real difference on variables length of study and student achievement index which is tested simultaneously by the activity of the regular students 2009 Public Health Faculty University of Sumatera with a significance value of Pillai’s Trace is 0,505 at 5% confidence level. For other studies were suggested to implement Two-Way MANOVA to test the effect of a set of independent variables to a set of dependent variables simultaneously.     Keyword: Two-Way MANOVA, Pillai’s Trace, student